For God and Country Essays on Religion and Nationalism - Mentzel, Peter C. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Religion and nationalism are both powerful and important markers of individual identity, but the relationship between the two has been a source of considerable debate. Much, if not most, of the early work done in Nationalism Studies has been based, at least implicitly, on the idea that religion, as a genealogical carrier of identity, was displaced with the advent of secular modernity, which was caused by nationalism. Or, to put it another way, national identity, and its ideological manifestation nationalism, filled the void left in people's self-identification as religion retreated in the face of modernity. Since at least the late 1990s, this view has been increasingly challenged by scholars trying to account for the apparent persistence of religious identities. Perhaps even more interestingly, scholars of both religion and nationalism have noted that these two kinds of self-identification, while sometimes being tense, as the earlier models explained, are also frequently coexistent or even mutually supportive. This collection of essays explores the current thinking about the relationship between religion and nationalism from a variety of perspectives, using a number of different case studies. What all these approaches have in common is their interest in complicating our understandings of nationalism as a primarily secular phenomenon by bringing religion back into the discussion.